Pengaruh Disiplin Kerja, Kepuasan Kerja, Dan Motivasi Kerja Terhadap Kinerja Karyawan Sebagai Variabel Moderasi CV. Shawn Printing Semarang - Widayat, Guruh Mulia; Sudarmin, Sudarmin (Magister Manajemen STIE Bank BPD Jateng, 2025)
This study aims to empirically test the influence of job satisfaction and work motivation on the performance of CV Shawn Printing Semarang employees. The population of this research is all employees of CV Shawn Printing Semarang. In this research, a total sampling technique was used; that is, the entire population was sampled. Then the data collection method is through questionnaires. The method used is quantitative with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. The number of respondents was 50 people with a minimum work period of one year.The research results show that work motivation has a significant positive effect on employee performance. Job satisfaction also has a significant positive impact on employee performance. Based on the coefficient of determination value of 0.649, which indicates that 64.9 percent of employee performance variables can be explained by work motivation and job satisfaction variables, while the remaining percentage is explained by other variables outside the scope of this research.